THE ROLE OF A TEACHER IN A STUDENT’S LIFE - Abdilboqiyeva Roziya Komil qizi (The latest pedagogical and psychological innovations in education, 2025)
This article explores the multifaceted role of a teacher in a student’s life. Beyond delivering academic content, teachers serve as mentors, motivators, and role models. The article discusses how teachers shape students’ intellectual growth, emotional development, and social behavior. It also highlights additional dimensions of modern teaching, including personalized instruction, technological integration, emotional support, and the promotion of lifelong learning. The article concludes that teachers are essential contributors to both individual success and the progress of society as a whole.